2004
DOI: 10.1111/j.1365-2125.2004.02154.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the pharmacokinetics of miconazole after administration via a bioadhesive slow release tablet and an oral gel to healthy male and female subjects

Abstract: AimsThe aim of this study was to compare salivary miconazole pharmacokinetics following once daily application of bioadhesive tablets (50 or 100 mg), vs the current treatment with a gel (3 times a day, 375 mg day -1 ). MethodsA three way cross over study was carried out in 18 healthy subjects (nine males, nine females) with a 1 week washout period between each treatment. Plasma and salivary pharmacokinetics of miconazole were assessed over a 24-h period. ResultsIn all subjects the tablets gave higher and more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 13 publications
2
28
0
Order By: Relevance
“…The increase of INR occurred 1-2 weeks after initiation of treatment with miconazole in previous report [6], which is compatible with the present case. Pharmacokinetic study with healthy volunteers also showed that the maximum plasma concentration of miconazole following repeated dosing of 125 mg oral gel formula was 0.4-1.0 lg/ml [7], which is comparable to our patient's result. We also found reduced bioavailability of CsA after termination of miconazole oral gel.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The increase of INR occurred 1-2 weeks after initiation of treatment with miconazole in previous report [6], which is compatible with the present case. Pharmacokinetic study with healthy volunteers also showed that the maximum plasma concentration of miconazole following repeated dosing of 125 mg oral gel formula was 0.4-1.0 lg/ml [7], which is comparable to our patient's result. We also found reduced bioavailability of CsA after termination of miconazole oral gel.…”
Section: Discussionsupporting
confidence: 79%
“…One possibility is absorption from intestine after swallowing. Oral miconazole gel dissolves in saliva [7]. Therefore, miconazole in swallowed oral gel and saliva might be absorbed from intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Miconazole in a 50 and 100 mg mucoadhesive tablet (miconazole Lauriad Âź ) formulated for extended release was initially tested in healthy volunteers [28]. Both concentrations were used once daily and had significantly longer duration and higher saliva concentration than a commercially available miconazole gel used three times per day.…”
Section: New Miconazole Formulationsmentioning
confidence: 99%
“…After stopping the medication for 14 days, the miconazole nitrate group showed a tendency toward a higher “cure” rate than the itraconazole group (42.01% vs. 32.14%, respectively), although the difference was not significant at the end of the treatment (31.36% vs. 29.17%, respectively). This might be related to the slow-release system with high, sustained salivary concentrations obtained with the mucoadhesive tablets [19]. In this study, we defined “cure” as clinical cure combined with mycological eradication.…”
Section: Discussionmentioning
confidence: 99%